Psychological Effects of Uncertainty - 10.7816/nesne-05-10-07 (Nesne Psikoloji Dergisi, 2017)
Uncertainty is defined in relation with concepts of incompetibility, unpredictability, misidentification, and dubiousness from different researchers in the literature. Also, need to reduce uncertainty is defined as a tendency to decrease uncertainties in order to gain certainty. The need to reduce uncertainty, which was proposed as a basic motivation from different researchers, is encountring frequently in daily life. In some cases, collective uncertainties follow daily uncertainties, which can be faced under normal conditions. Collective uncertainties include both cultural tendencies related with uncertainty and collectively experienced uncertainties. Turkey’s cultural tendency to avoide uncertainty and collective events including uncertainties experienced recently such as terrorist attacts and coup attempt increase impact of the topic for Turkey. In this paper, aim is to introduce psychology of uncertainty and examine uncertain events experienced in Turkey. It was emphasized that strategies to reduce uncertainty become unfunctional in some cases in our country. For this reason, new strategies which can be usefull to reduce uncertainty in Turkey were suggested as (a) introducing uncertainty as manageable with respect to positive uncertainty experiences, (b) giving exact information under uncertain conditions, and (c) presenting peacefull speeches considering possible intergroup conflicts result from uncertainty management.